PENGEMBANGAN PROGRAM AUTO ECONOMY MODE BERBASIS PLC UNTUK EFISIENSI BAHAN BAKAR DUMP TRUCK HD 785 - Tri Wahyu Oktaviana Putri; Kartika Tresya Mauriraya; Teguh Juwono (Sutet, 2018)
This research aims to design an automation system on Dump truck as fuel efficiency effort. The existence of control of fuel efficiency will be very helpful in reducing cost / budget expenditure on each company. Auto Economy mode is an automatic system in the mode of activation (power mode or economy mode) in accordance with the state of the unit load. When the unit is loaded heavy then the system will automatically turn on the power mode. And then, when the unit is not charged, the system will automatically activate the economy mode. Automatic operation of 2 modes would require an enhancement as a controller. In the Auto Economy mode HD785-7 used PLC as a controller.